Comparative analysis of bulk ceramics and thick film coatings for optimized energy storage technologies - Imran Hussain Khan; Muhammad Salman Habib; Adnan Maqbool; Muhammad Asif Rafiq; Amjad Ali; Khushnuda Nur; Aqil Inam; Nasimullah; Vojtech Blazek; Stanislav Misak (Scientific Reports)
Abstract The present investigation provides an easy and affordable strategy for fabrication of functional ceramics Bi0.5Na0.5TiO3-SrFe12O19 (BNT-SrF5) thick films on a flexible, inexpensive and electrically integrated substrate using electrophoretic deposition process (EPD). EPD is a widely accepted, environmentally friendly method for applying coatings from a colloidal suspension to conductive substrates. Lead-free ferroelectric BNT-SrF5 powder was synthesized by solid state method to fabricate bulk samples and thick films (30–160 μm) by EPD process. Thick films were deposited onto nickel substrate by applying EPD parameters, i.e. voltage (225–290 V) and coating time (30–180 s) to acetone based colloidal suspension without aid of any dispersing agent. In a comparative analysis, both thick films and bulk ceramics revealed significant densification with sintering temperature from 1025 to 1150 °C. Fourier transform Infrared (FTIR) and X-ray diffraction (XRD) analysis revealed presence of distorted perovskite structure following calcination and sintering processes. Scanning electron microscopy (SEM) provided the surface morphologies of BNT-SrF5 powder. The dielectric constant of film sample revealed more thermal stable response compared to the bulk ceramics. Impedance spectroscopy explained the electrically active regions and hopping conduction mechanism which witnessed NTCR behavior. The potential applications for the miniaturization of electronics are sensors, actuators and energy harvesting devices.